A didactic perspective on negotiations and collaborations between different actors within the Swedish support system: children with autism spectrum disorders included in community-based preschool settings. Issue 1 (2nd January 2020) - Olsson, Ingrid; Roll-Pettersson, Lise
ABSTRACT: In the present study, a didactic perspective was used to examine collaborations and negotiations between preschools and habilitation centres concerning intensive behavioural interventions for children with autism spectrum disorders in inclusive settings in Swedish preschools. The didactic triangle was used as the theoretical tool to analyse information derived from a qualitative case-study in two preschools exemplifying 'high quality practice'. Direct content analysis was used to analyse data with a focus on the child, the pedagogue, and the subject. Data were collected through multiple sources during a 12-month period, including observations and interviews. A model of aspects of the collaboration between preschools, habilitation centres, and families was conceptualized based on the didactic triangle: the 'pedagogue cornerstone' encompassed competence, attitudes, and collaborations; the 'child cornerstone' encompassed learning in relation to specific goals; the 'subject cornerstone' encompassed both subjects shared with typically developing peers and subjects related to the specific challenges. In addition, the preschool principals were described as important. Different factors in relation to tensions and collaborations between organizations concerning inclusive education were elaborated. Implications for preschools, inter-organizational collaboration, and future research are discussed.